IMPLIKASI HUKUM BAGI PENERIMA DALAM PELANGGARAN TINDAK PIDANA POLITIK UANG PADA PEMILIHAN KEPALA DAERAH - Baehaqi, Eki Sirojul; Epa (Jurnal Keadilan Pemilu, 2024)
The practice of money politics that occurs in the election of Regional Heads is a form of violation or criminal act of the election. Money politics can damage the democratization process, but this seems to have become a bad culture in society and is considered commonplace. The purpose of this study is to determine the legal regulations and consequences for recipients involved in the practice of money politics and what efforts should be made. This research method is a normativeresearch that is descriptive-analytical with a normative legal approach. The results of the study indicate that the practice of money politics is a form of criminal act of the election and recipients involved in the practice of money politics are qualified as perpetrators (dader) who can be held accountable for criminal acts of the same degree as the giver of money or promises.